Penggunaan Media Sosial Instagram Sebagai Media Dakwah Mahasiswa Komunikasi Penyiaran Islam Uinsu - Rafly Surya Dharma; Efendi, Erwan; Afriana Alawiah. AR; Dila Fitria; Miftahul Anwar Alamsyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social media is one of the information media that exists today, social media users come from various circles, from 9 year old children to adults, using social media requires vigilance, especially as parents, you must provide education to children, because through media Children can get positive sides from social media, such as interesting learning, but through social media there are also many negative sides, therefore there is a need for a high level of supervision over the use of social media. To make social media a medium that provides a positive side, there must be more content about da'wah, so in this research study Islamic broadcasting students create da'wah content through social media, how to spread their da'wah will be studied further in the discussion. The method used is literature and the type of research is qualitative. Based on the research results, the use of social media Instagram as a medium for Islamic broadcasting communication for students of Islamic broadcasting. Instagram social media is very influential for students of Islamic broadcasting communication, because Instagram social media can make preaching more interesting. And students can develop their existing talents and potential.